Effect of Potassium Chloride on Seed Germination and Early Growth of Three Rape Seed Varieties - Shakeela Bano Solangi; Zeeshan Ahmed Solangi; Afshan Bano Solangi; Shabana Memon; Jameel Ahmed Solangi; Sadaf Memon (Journal of Basic & Applied Sciences, 2018)
Salinity stress is one of the crucial factors affecting at different stages of growth and development of the crop. In the present research, the seeds of three rape seed varieties like Toria selection, Sindh Raya and Sarhein-95 were exposed to increasing concentrations (1 and 2%) of KCl to demonstrate the effect of salt stress on seed germination and early seedling growth of rape seed varieties. Seed germination and seedling growth decreased with the increase of KCl grown in Petri dishes within seven days. Highest germination and seedling growth was recorded in Sindh Raya than Toria and Sarhein-95. On the basis of all growth characteristics, the three genotypes were found to be more sensitive under KCl salt stress.